KAJIAN SASTRA ANAK: KONTRIBUSI NILAI PERSONAL DAN NILAI PENDIDIKAN DALAM BUKU CERITA SI BUNCIR KARYA ASEP RAHMAT HIDAYAT - Rohmah, Dwi Putri Khabibatur; Putri, Aurelia Theysa; Agustian, Muhammad Ilham; Erfansyah, Muhammad; Setiawaty, Rani (INOPENDAS: Jurnal Ilmiah Kependidikan, 2024)
This study aims to analyze the personal values and educational values contained in the children's story "The Buncir" by Asep Rahmat Hidayat. The story "Si Buncir" is a fairytale genre that has many moral messages for readers and as an alternative learning in conveying messages to elementary students. The research method used is a qualitative descriptive approach. The research data is the story script "The Buncir". Data collection techniques were carried out using literature study techniques, while data analysis techniques used content analysis with the results described in a narrative manner. Based on the results of the study it was found that, First, personal values include emotional development, intellectual development, imagination development, social sense growth, and ethical and religious sense growth. Second, educational values include religious values, honesty, discipline, independence, curiosity, democracy, responsibility. Thus, this children's story book provides messages and moral lessons about character that can be emulated by children, especially elementary school children, both in terms of developing personal values and character education values.